Digital Learning Ecosystem at Indian Higher Education System - Bhatnagar, Anjani Kumar; Khanna, Dr. Uday; Rana, Dr. Ajay (The journal of contemporary issues in business and government, 2021)
Within a fleeting period, Digital Learning Tools and Applications, have taken a contemplative space in the lives of every individual, across all spheres ranging from homes to offices, education to businesses. This study investigates the significance and the contribution of Artificial Intelligence enabled Learning Tools in dealing with VUCA world challenges at the Indian Higher Education Institutions. Digital Learning Ecosystem will be a gamechanger in mounting the reputation of the Indian Education System by offering best-in-class education to every citizen envisaged through National Education Policy 2020 across the nation. Optimization of AI-enabled teaching-learning tools in India demands strong strategies, training, and investment through public-private initiatives. Artificial Intelligence- powered Digital platforms will flourish in Indian Education System but there will be a compelling need for a strong & viable heterogeneous paradigm to meet the expectations of students and raise the bar of teaching being divulged to students in India.